Sobetirome-Loaded Chitosan Nanoparticles for Controlled Release and Enhanced Blood-Brain Barrier Permeability in Neurodegenerative Disorders - Penceci, Buse; Ustundag, Cem Bulent; Cakir, Rabia (WILEY-V C H VERLAG GMBH, 2026)
Neurodegenerative diseases represent a major global health challenge due to their progressive nature and lack of curative therapies. Developing innovative strategies to protect and regenerate neuronal structures is therefore crucial. In recent years, Sobetirome, a synthetic thyromimetic compound, has emerged as a promising therapeutic candidate for neurodegenerative disorders owing to its neuroprotective and regenerative potential. However, its clinical efficacy is limited by the poor permeability of the blood-brain barrier. Enhancing brain delivery through controlled transport systems could therefore improve therapeutic outcomes. In this study, Sobetirome was encapsulated into chitosan-based nanoparticles to enhance its stability, bioavailability, and blood-brain barrier penetration. An in vitro neurodegeneration model was established using SH-SY5Y cells treated with lysophosphatidylcholine, and a Caco-2 cell line was used to evaluate blood-brain barrier permeability. The nanoparticles showed an average size of 137.7 nm, a low polydispersity index (0.1), and a zeta potential of +21 mV, indicating stability and uniformity. FTIR analysis confirmed successful drug encapsulation, while encapsulation and loading efficiencies reached 91.2% and 65.15%, respectively. In vitro release studies demonstrated a controlled release profile, with 73.39% of Sobetirome released after 32 h. Cellular assays revealed that Sobetirome-loaded nanoparticles enhanced SH-SY5Y cell viability, proliferation, neuroprotection, and regenerative effects compared to free Sobetirome. Lower nanoparticle concentrations reduced apoptosis and improved cellular uptake. SEM imaging confirmed spherical morphology and nanoscale dimensions, consistent with DLS measurements. Overall, these results suggest that Sobetirome-loaded chitosan nanoparticles are a promising platform for neurodegenerative disease therapy, providing improved bioavailability, controlled drug release, and potential for systemic delivery to optimize therapeutic outcomes.
Keywords: BBB; chitosan nanoparticles; neurodegenerative disorders; sobetirome; IN-VITRO; DRUG-PERMEABILITY; CACO-2 MONOLAYER; DELIVERY; NEUROTRANSMITTER; METABOLISM; ABSORPTION; DAPI; Biochemistry & Molecular Biology; Materials Science; Polymer Science